Long-term clinical outcomes of Entecavir and .tenofovir in hepatitis B cirrhosis - Koklu, Seyfettin; Tuna, Yasar; Gulsen, Murat T.; Demir, Mehmet; Koksal, Aydin S.; Kockar, Muhammed C.; Yuksel, Osman (Wiley-Blackwell, 2012)
[Abstract Not Available]
63rd Annual Meeting of the American-Association-for-the-Study-of-Liver-Diseases (AASLD) -- NOV 09-13, 2012 -- Boston, MA